Regional peculiarities of malacofauna in waterbodies of different types of the North-West Azov Sea Coast - Khaliman, I. A.; Anistratenko, V. V.; Degtyarenko, E. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The study of the species diversity and the distribution of molluscs in fresh and brackish waters of the North-West Azov Sea coast reveals some peculiarities of molluscan associations in the Utlyukskij liman, Eastern part of the Lake Sivash, and rivers of the Northern-West part of the Sea of Azov basin. The hydrological regime of the Utlyukskij liman determines the stable existence and the most complete similarity of malacofauna of this reservoir and the Sea of Azov. The Lake Sivash has considerably impoverished and trivial fauna, while the rivers of the NW part of the Sea of Azov basin demonstrate a wide range of species composition and categories of occurrence of freshwater molluscs. The most transformed so far regional reservoirs are the Northern part of the Utlyukskij liman and the majority of the small rivers of the NW Azov Sea coast. The animal population of the waters of the Eastern Sivash most dynamically responds to sharp fluctuations in salinity and watering through the redistribution of the basic clusters of the fauna of the local and adjacent habitats.